PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING CHIPS UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI MIPA SMA NEGERI 4 PEKANBARU - Putri, Rahma; Yasmi, Elva; Noer, Asmadi M (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the increase in student learning outcomes by applying cooperative learning models talking chips type on the subject of Reaction Rate in class XI MIPA SMAN 4 Pekanbaru. The form of this study uses the Pretest-Postest Design Randomized Control Group. The sample consisted of class XI MIPA 1 as the experimental class and XI MIPA 2 as the control class which was randomly selected after the normality test and homogeneity test. The experimental class is a class that applies the cooperative learning model of talking chips. The data analysis technique uses test techniques. Testing the hypothesis using the T test with a = 0.05 obtained by Tcount > Ttable (1.89 >1.66). Based on hypothesis testing it was concluded that the application of cooperative learning models talking chips type can improve student learning outcomes on the subject of reaction rate in class XI MIPA SMAN 4 Pekanbaru.Key Words: Cooperatve Learning Models Type Talking Chips, Learning Outcomes, Reaction Rate